Optimal contract orders and relationship-specific investments in vertical organizations - Sarah Parlane; Ying-yi Tsai (University College Dublin, UCD School of Economics, 2013)
This paper characterizes the optimal contracts issued to suppliers when delivery is subject to disruptions and when they can invest to reduce such a risk. When investment is contractible dual sourcing is generally optimal because it reduces the risk of disruption. The manufacturer (buyer) either issues symmetric contracts or selects one supplier as a major provider who invests while the buffer supplier does not. An increased reliance on single sourcing or on a major supplier is optimal under moral hazard. Indeed, we show that order consolidation increases the manufacturer's profits because it serves as an incentive device in inducing investment.
Keywords: D23; D86; L24; 330; Moral Hazard; Vertical Organization; Supply Base Management; Contract Order Size; Relationship-specific Investment; Strategic Outsourcing